Potential Genotoxicity of Alkaloids: A Review Article - Faris Hassan, Ali; Alshawi, Nada Naji; Rasheed, Myriam (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Any harm done to genetic material, whether directly interacting with DNA or indirectly through biological systems, is referred to as genotoxicity. Such harm poses major risks to the health of people, animals, and plants as it is a primary source of carcinogenesis, mutagenesis, and teratogenesis. Because of their medicinal qualities, alkaloids—a family of naturally occurring phytochemicals made by plants from amino acids—are frequently utilized to treat ailments such newborn apnea, gout, and asthma. Recent research has sparked worries about their possible genotoxic consequences despite their therapeutic advantages. Through a variety of processes, including as the creation of DNA adducts, DNA–DNA cross-links, and DNA–protein cross-links, alkaloids have been demonstrated to cause chromosomal abnormalities. These processes can all impede DNA replication, transcription, and repair. The aims to investigate and compile the most recent scientific findings about the genotoxic potential of alkaloids, emphasizing both the hazards of prolonged exposure and the molecular mechanisms of action. Along with highlighting the pervasive and frequently uncontrolled use of plant-based remedies under the false pretence of safety, it also seeks to distinguish genotoxicity from similar ideas like mutagenicity and teratogenicity. In conclusion, alkaloids have significant therapeutic potential; however, care is advised due to their potential to harm genetic material. Standardized testing procedures like the Ames, comet, and micronucleus tests are necessary to provide a more thorough knowledge of their genotoxic processes. This knowledge is essential for risk assessment as well as for directing the safe use of treatments containing alkaloids in both conventional and clinical medicine.